A estratégia revolucionária gramsciana: uma maturação política work in progress - Siqueira, Mirele Hashimoto (2019)
The present dissertation established as its theme of scientific research Antonio Gramsci's revolutionary strategy, proposing to answer the following guiding problem: In the Prison Notebooks and manifested in the modern prince, do they have a relation of continuity with each other? elaboration of the political party, expressed in the modern prince, in Prison Notebooks. To ensure its viability, we set as specific objectives: 1) to identify the revolutionary strategy developed by Gramsci in the Turin period of the biennio rosso and expressed in the Factory Councils; 2) identify the revolutionary strategy elaborated by Gramsci in the Prison Notebooks and expressed in the modern prince; 3) to analyze the continuity relations present between the theoretical and practical elaboration of the biennio rosso's revolutionary advisory strategy and that of the revolutionary strategy of the Prison Notebooks manifested in the modern prince. Thus, using exploratory, bibliographical and qualitative research, the research affirms the inseparability between the biennio rosso and the Notebooks mainly in Gramsci's theoretical elaboration. We can only understand the presupposition of inseparability when we understand that its theoretical and practical elaborations are part of a continuous process of political maturation - a path from which it has been traveled and must be followed.